LEGAL PERSPECTIVES ON THE CONFISCATION OF CORRUPTION ASSETS: IMPLICATIONS FOR JUSTICE AND HUMAN RIGHTS - Thaifur Rasyid; Sunardi; Nofi Sri Utami (International Journal of Cultural and Social Science, 2025)
This study examines the legal impact of the policy on the confiscation of assets derived from corruption on human rights in Indonesia, focusing on property rights and the presumption of innocence. A qualitative approach is used, combining normative legal analysis with empirical case studies through observation and documentation of asset confiscation cases in Indonesia. The findings indicate that while asset confiscation is a key tool in fighting corruption, its implementation faces legal challenges that jeopardize citizens' constitutional rights. Issues include asset confiscation without a final court decision (inkracht) and inadequate legal protection for third parties acting in good faith. The study suggests the need for policy reforms to strengthen evidence mechanisms, improve transparency, ensure independent oversight, and offer clearer legal protections. These reforms are essential to balancing the fight against corruption with respect for human rights in Indonesia’s legal system. Further research should focus on empirical case examples and a broader theoretical discussion.